Sirt3-Mediated Autophagy Contributes to Resveratrol-Induced Protection against ER Stress in HT22 Cells - Yan, Wen-Jun; Liu, Ruo-Bin; Wang, Ling-Kai; Ma, Ya-Bing; Ding, Shao-Li; Deng, Fei; Hu, Zhong-Yuan; Wang, Da-Bin (Frontiers in Neuroscience, 2018)
Endoplasmic reticulum (ER) stress occurring in stringent conditions is critically involved in neuronal survival and death. Resveratrol is a non-flavonoid polyphenol that has neuroprotective effects against many neurological disorders. Here, we investigated the potential protective effects of resveratrol in an in vitro ER stress model mimicked by tunicamycin (TM) treatment in neuronal HT22 cells. We found that TM dose-dependently decreased cell viability and increased apoptosis, which were both significantly attenuated by resveratrol treatment. Resveratrol markedly reduced the expression or activation of ER stress-associated factors, including GRP78, CHOP and caspase-12. The results of immunocytochemistry and western blot showed that resveratrol promoted autophagy in TM-treated cells, as evidenced by increased LC3II puncta number, Bcelin1 expression and LC3II/LC31 ratio. Pretreatment with the autophagy inhibitor chloroquine could reduce the protective effects of resveratrol. In addition, the expression of Sirt3 protein and its downstream enzyme activities were significantly increased in resveratrol-treated HT22 cells. To confirm the involvement of Sirt3-mediated mechanisms, siRNA transfection was used to knockdown Sirt3 expression in vitro. The results showed that downregulation of Sirt3 could partially prevented the autophagy and protection induced by resveratrol after TM treatment. Our study demonstrates a pivotal role of Sirt3-mediated autophagy in mediating resveratrol-induced protection against ER stress in vitro, and suggests the therapeutic values of resveratrol in ER stress-associated neuronal injury conditions.